The Genetic Spectrum of Familial Hypertriglyceridemia in Oman - Al-Waili, Khalid; Al-Rasadi, Khalid; Al-Bulushi, Muna; Habais, Mohammed; Al-Mujaini, Abdullah; Al-Yaarubi, Saif; Rimbert, Antoine; Zadjali, Razan; Khaniabadi, Pegah Moradi; Al-Barwani, Hamida; Hasary, Sana; Al-Dahmani, Zayana M.; et al. (Frontiers in Genetics, 2022)
Familial hypertriglyceridemia (F-HTG) is an autosomal disorder that causes severe elevation of serum triglyceride levels. It is caused by genetic alterations in LPL, APOC2, APOA5, LMF1, and GPIHBP1 genes. The mutation spectrum of F-HTG in Arabic populations is limited. Here, we report the genetic spectrum of six families of F-HTG of Arab ancestry in Oman. Methods: six Omani families affected with triglyceride levels >11.2 mmol/L were included in this study. Ampli-seq sequencing of the selected gene panels was performed. Whole-exome sequencing and copy number variant analysis was also performed in cases with negative exome results. Three novel pathogenic missense variants in the LPL gene were identified p.M328T, p.H229L, and p.S286G along with a novel splice variant c.1322+15T>G. The LPL p.H229L variant existed in double heterozygous mutation with the APOA5 gene p.V153M variant. One family had a homozygous mutation in the LMF1 gene (c.G107A; p.G36D) and a heterozygous mutation in the LPL gene (c.G106A; p.D36N). All affected subjects did not have a serum deficiency of LPL protein. Genetic analysis in one family did not show any pathogenic variants even after whole-exome sequencing. These novel LPL and APOA5 mutations are not reported in other ethnic groups. This suggests that patients with F-HTG in Oman have a founder effect and are genetically unique. This warrant further analysis of patients of F-HTG in the Middle East for preventative and counseling purposes to limit the spread of the disease in a population of high consanguinity.